2010
DOI: 10.1007/s10067-010-1562-8
|View full text |Cite
|
Sign up to set email alerts
|

Case report: successful use of short-term add-on tocilizumab for multirefractory systemic flare of adult-onset Still’s disease

Abstract: We report on a 64-year-old woman with multirefractory flare of adult-onset Still's disease successfully treated with six-month course of add-on anti-interleukin 6 receptor antibody, tocilizumab. Before administration of tocilizumab, the combination therapy with 80 mg/day of prednisolone and cyclosporine or tacrolimus for five weeks, two courses of pulse methylprednisolone, and high-dose intravenous immunoglobulin could not control the disease. Add-on tocilizumab dramatically improved her disease state and enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In addition, serum IL6 level after administration of tocilizumab, which is known to increase more and reflect the actual endogenous IL6 production much better than the serum IL6 level before tocilizumab treatment [9], showed an increase at day 5 after administration of tocilizumab (29.6 pg/mL) but thereafter promptly decreased to within-normal range. In our previous case report of the AOSD patient successfully treated by tocilizumab, serum IL6 level showed a significant increase 14 days after the start of tocilizumab (166 pg/mL) compared to just before administration of tocilizumab (12.2 pg/mL), then reached the highest value after 71 days (365 pg/mL), and thereafter decreased to 43.8 pg/mL just before successful withdrawal of tocilizumab treatment [10]. Therefore, it is suggested that IL6-driven inflammation was already efficiently suppressed during the treatment with high-dose corticosteroids and cyclosporine in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serum IL6 level after administration of tocilizumab, which is known to increase more and reflect the actual endogenous IL6 production much better than the serum IL6 level before tocilizumab treatment [9], showed an increase at day 5 after administration of tocilizumab (29.6 pg/mL) but thereafter promptly decreased to within-normal range. In our previous case report of the AOSD patient successfully treated by tocilizumab, serum IL6 level showed a significant increase 14 days after the start of tocilizumab (166 pg/mL) compared to just before administration of tocilizumab (12.2 pg/mL), then reached the highest value after 71 days (365 pg/mL), and thereafter decreased to 43.8 pg/mL just before successful withdrawal of tocilizumab treatment [10]. Therefore, it is suggested that IL6-driven inflammation was already efficiently suppressed during the treatment with high-dose corticosteroids and cyclosporine in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that the exact role in disease modification with anti-CD-20 therapy hasn't been surveyed in these patients yet evidences have shown that following B cell depletion with rituximab treatment, a decrease was observed for IL-1b, IL-1RA, IL-2R, IL-4, IL-5, IL12, IL-15, IL-17, TNF-α, GM-CSF for 24 weeks with partial recovery over a period of 24 -48 weeks which suggests that B cell depletion might down regulate the release of T cell mediated pro-inflammatory cytokine release [9][10][11][12][13]. Considering that the exact pathogenesis of ASD remains poorly understood, therefore encouraging trials addressing the use of different lines of biologic disease modifying drugs in patients with AoSD might provide further insight into the pathogenesis of this complex disease.…”
Section: Resultsmentioning
confidence: 99%
“…The goal of treatment in patients with ASD is not solely focused on treating joint symptoms but also targets the systemic manifestations of the disease. With the new era of biologic therapy (Biologic disease modifying anti-rheumatic drugs), anti-tumor necrosis factor alpha therapy, anti-IL-1 therapy and recently anti-IL-6 are highly recommended in patients with chronic systemic activity who are considered refractory to traditional DMARDs [7][8][9][10][11][12][13]. Trials studying the use of anti-CD-20 (rituximab) in conventional DMARD non-responders with systemic onset rheumatoid arthritis (ASD) are lacking with only two case reports displaying efficacy of the drug in refractory cases who failed anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[2025] On the other hand, anti-TNFα agents were not effective in patients with refractory AOSD. [26] Therefore, anakinra and tocilizumab have been recently recommended for refractory systemic AOSD.…”
Section: Discussionmentioning
confidence: 99%